Efficiency of complex application of fertilizers in fodder crop rotation on sod-podzolic soil in the conditions of middle taiga zone of the Euro-North-East - N. T. Chebotarev (Аграрная наука Евро-Северо-Востока, 2017)
In a field stationary experiment on sod-podzolic light-loamy soil the efficiency of organic and mineral fertilizers and their combinations on the fertility and productivity of soil were examined. The best results were obtained by joint application of (TNC 80 t/ha) and mineral fertilizer (1 NPK). The average yield of potato for 2 crop rotation was 3.9, of annual grasses - 4.4, and of perennial grasses 6.6 t/ha of dry matter respectively. It is revealed that organic-mineral system of fertilizing promoted the increase in the starch content in potatoes to 13.13.6% (in control - 10.3 and 11.6%). Organic and organic-mineral systems of fertilizing had positive influence on content of soil organic matter. For 1978.2015 humus content is increased by 0.7.0.9% at using TNK (40 and 80 t/ha) and by 0.3.0.5% at complex use of organic and mineral fertilizers. At using of different doses of mineral fertilizers the humus content in the soil decreased by 0.1.. .0.2%